2020
DOI: 10.3390/cells9010146
|View full text |Cite
|
Sign up to set email alerts
|

miR-26a is Involved in Glycometabolism and Affects Boar Sperm Viability by Targeting PDHX

Abstract: miR-26a is associated with sperm metabolism and can affect sperm motility and apoptosis. However, how miR-26a affects sperm motility remains largely unknown. Our previous study indicated that the PDHX gene is predicted to be a potential target of miR-26a, which is responsible for pyruvate oxidative decarboxylation which is considered as a key step for connecting glycolysis with oxidative phosphorylation. In this study, we first reported a potential relationship between miR-26a and PDHX and their expressions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 86 publications
1
12
0
Order By: Relevance
“…These results suggest that the critical role and function of piRNAs during spermatogenesis process has been well documented, whether piRNAs in sperm may regulate sperm motility remain largely unknown. Increasing studies have shown that miRNAs expressed in mature sperm could regulate sperm motility ( 25 , 26 ). In contrast to miRNAs, piRNAs were just discovered in 2006, and the biogenesis and functions remain largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the critical role and function of piRNAs during spermatogenesis process has been well documented, whether piRNAs in sperm may regulate sperm motility remain largely unknown. Increasing studies have shown that miRNAs expressed in mature sperm could regulate sperm motility ( 25 , 26 ). In contrast to miRNAs, piRNAs were just discovered in 2006, and the biogenesis and functions remain largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…8 Further, miR-26a promotes boar sperm viability and survival by targeting the pyruvate dehydrogenase complex component X gene through the glycometabolic pathway. 32 However, it is essential to gain additional insights into the roles of miRNAs in porcine Sertoli cell proliferation. Therefore, in this study, we detected the effect of 60 miRNAs on porcine Sertoli cell proliferation using EdU-based high-content screening assays.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR‐762 promotes porcine immature Sertoli cell growth by targeting the ring finger protein 4 gene 8 . Further, miR‐26a promotes boar sperm viability and survival by targeting the pyruvate dehydrogenase complex component X gene through the glycometabolic pathway 32 . However, it is essential to gain additional insights into the roles of miRNAs in porcine Sertoli cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Before total RNA extraction, seminal plasma was removed by centrifuged for 5 min at 4000 rpm and washed with phosphate buffer solution (PBS) for three times. To eliminate somatic cell contamination, sperm pellet was treated with 0.5 % Triton X-100 (Coolaber, Beijing, China) [ 109 ]. Then, Total RNA from boar sperm was extracted with Trizol LS Reagent (Invitrogen Corporation, Carlsbad, CA, USA) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot of METTL3, METTL14, FTO, ALKBH5 and YTHDF2 was performed according to previous report [ 109 ] with some modifications. Briefly, after seminal plasma was removed, sperm pellets were resuspended in a RIPA buffer (containing 1 % phenylmethylsulfonyl fluoride), placed on ice for 30 min and then centrifuged at 12,000 rpm, 4 °C, for 5 min.…”
Section: Methodsmentioning
confidence: 99%